2019
DOI: 10.1108/add-05-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a dominant discourse in fetal alcohol spectrum disorder

Abstract: Purpose The purpose of this paper is to conduct a scoping review of the literature to explore the many ways stigma affects people with FASD and to highlight the disciplines and places where discourse on FASD and stigma is taking place. Design/methodology/approach Searches were conducted in PubMed, ERIC, Family & Society Studies Worldwide, Families Studies Abstracts and Google Scholar between 2008 and 2018. Search terms focused on stigma, shame and the connection to FASD with a view to looking across soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…Professionals have a key role in stigma reduction through FASD-informed practice. This means a solid grounding in knowledge on FASD from a family systems perspective and engagement in trauma-informed practice while building supportive relationships with families and communities [36].…”
Section: Discussionmentioning
confidence: 99%
“…Professionals have a key role in stigma reduction through FASD-informed practice. This means a solid grounding in knowledge on FASD from a family systems perspective and engagement in trauma-informed practice while building supportive relationships with families and communities [36].…”
Section: Discussionmentioning
confidence: 99%
“…The data also indicates that formal support is an important source of support and knowledge. Choate and Badry [10] found that stigma is a major concern in how women experience interactions with professionals and formal support. Thus, if mothers are able to connect with these supports, that connection is likely to be sustained if the mother is accepted even when struggling with continuing use.…”
Section: Discussionmentioning
confidence: 99%
“…Harm reduction might be one such opportunity. This is worth exploring in more detail as it may shift away from abstinence and stigmatizing messages [10] to ones where traumatized populations may be able to see their lived realities in the messages [27]. This may include acknowledging environmental factors that contribute to the ongoing alcohol use in this population, such as homelessness and lack of social support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations